Towards agro-environmentally sustainable irrigation with treated produced water in hyper-arid environments - Echchelh, Alban; Hess, Tim M.; Sakrabani, Ruben; Prigent, Stephane; Stefanakis, Alexandros I. (Elsevier, 2020)
1. Introduction The extraction of oil and gas (O&G) is accompanied by massive volumes of produced water (PW), which is composed of formation water initially present in the hydrocarbon reservoir and also water that has been injected during O&G operations and comes back to the surface (such as water injected for enhanced oil recovery and hydraulic fracturing) (Engle et al., 2014). By volume, PW is the main by-product associated with the O&G industry (Veil, 2011) and its volume is increasing (Hedar and Budiyono, 2018; Nasiri et al., 2017). In the southeast Arabian Peninsula, for instance, the volume of PW generated by the O&G industry was estimated at 330,000 m3/day in 1997 (Al-Muscati et al., 1997), but is predicted to exceed 1 million m3/day in 2019 (Prabhu, 2018).
Keywords: Arid climate; Irrigation water quality; Modelling; Oil; Salinity; SALTIRSOIL